2009
DOI: 10.1002/pmic.200700583
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin modifies the protein profile of circulating human monocytes after an acute coronary syndrome

Abstract: Aggressive treatment with high-dose atorvastatin reduces more effectively the incidence of cardiovascular events than moderate statin therapy. The mechanism of this benefit has not been fully elucidated. In order to know the potential effects of statin treatment on the protein expression of circulating monocytes in acute coronary syndrome (ACS) patients, a proteomic analysis of these cells was carried out by 2-DE and MS. Twenty-five patients with non-ST-elevation acute coronary syndrome (NSTEACS) were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 56 publications
2
12
0
1
Order By: Relevance
“…In contrast, there was overexpression of mature cathepsin D, with pro-atherogenic effects and enolase I, involved in macrophage transformation into foam cells. Other studies in the same context confirm that, in NSTE-ACS patients, atorvastatin 80 mg/day normalizes expression of HSP70, paraoxonase I, annexin I-which has antiinflammatory properties-and annexin II-involved in spontaneous fibrinolysis (Barderas et al, 2009). It has previously been shown that cathepsin D and HSP70 are biomarkers of atherosclerotic lesions .…”
Section: Proteomics: the Current Center Of Attentionsupporting
confidence: 60%
“…In contrast, there was overexpression of mature cathepsin D, with pro-atherogenic effects and enolase I, involved in macrophage transformation into foam cells. Other studies in the same context confirm that, in NSTE-ACS patients, atorvastatin 80 mg/day normalizes expression of HSP70, paraoxonase I, annexin I-which has antiinflammatory properties-and annexin II-involved in spontaneous fibrinolysis (Barderas et al, 2009). It has previously been shown that cathepsin D and HSP70 are biomarkers of atherosclerotic lesions .…”
Section: Proteomics: the Current Center Of Attentionsupporting
confidence: 60%
“…With a similar approach we showed that atorvastatin 80 mg/day affected the expression of 20 proteins in NSTEACS patients as compared with moderate statin therapy (29). Among them, there was a normalization of the decreased expression of HSP70, paraoxonase I, annexin I-which has anti-inflammatory properties-and annexin II-involved in spontaneous fibrinolysis.…”
Section: The Study Of Blood By Proteomic Approachesmentioning
confidence: 54%
“…Proteomic studies performed to date in atherosclerosis involve plasma (13), circulating cells (particularly monocytes) (14,15), and atherome tissue analysis (7). Proteomic analysis of atherome tissue has been mostly carried out by studying the tissue as a whole.…”
Section: Discussionmentioning
confidence: 99%